Investigation of antifungal potency of capsaicin and tea tree oil against oral infection in pediatric patients - Zakeeyah Saliam Mohammed Qajjam; Rumadhanah Abraheem Mohammed (African Journal of Advanced Pure and Applied Sciences, 2026)
Oral fungal infections, primarily caused by Candida species, are prevalent in pediatric patients. The antifungal efficacy of capsaicin and tea tree oil appears promise; however, their efficiency against Candida species in oral infections has been largely unexamined. This study evaluated the antifungal efficacy of capsaicin and tea tree oil against Candida albicans and Candida tropicalis in pediatric patients with oral fungal infections. This is a cross-sectional, laboratory-based investigation conducted from March to June 2024. The study included children aged 2 weeks to 24 months diagnosed with oral Candida infections. Oral swabs were collected from the diseased areas, and Candida species were identified with Sabouraud Dextrose Agar, germ tube assays, and CHROMagar Candida. Antifungal susceptibility testing was conducted against capsaicin and tea tree oil using a twofold serial dilution in liquid media. This study included 30 children, predominantly male (55%), aged between 6 and 12 months. Of the identified Candida species, Candida albicans comprised 70%, while Candida tropicalis constituted 30%. Maternal attributes indicated that 40% of mothers possessed a high school education, whilst 60% participated in breastfeeding. Capsaicin and tea tree oil exhibited antifungal properties, with capsaicin demonstrating superior fungicidal efficacy, especially against Candida albicans. Conversely, tea tree oil shown activity, mostly in a fungistatic capacity, against Candida tropicalis. Capsaicin and tea tree oil have antifungal properties against Candida albicans and Candida tropicalis, with capsaicin proving to be more effective. These natural compounds may serve as supplementary therapy to conventional antifungals in pediatric oral infection cases.